2018
DOI: 10.1002/pd.5253
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing cardiac dysfunction in fetuses with left congenital diaphragmatic hernia

Abstract: Left CDH fetuses show echocardiographic signs of diastolic dysfunction, probably secondary to fetal heart compression, maintaining a preserved systolic function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Recently, Mod-MPI has been reported to be a valuable index for evaluating fetal cardiac function and it has been evaluated as an indicator for predicting pregnancy outcomes in a number of studies. [15][16][17][18][19][20][21][22][23] Evaluation of Mod-MPI depends on comparison to a normal reference ranges, so a large multicentre study using standardised machine settings and techniques with well-defined inclusion and exclusion criteria is still required, which forms the basis of this study. The primary aim of this study was to establish the normal reference ranges of fetal left ventricular (LV) Mod-MPI and time intervals by pulsed…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Mod-MPI has been reported to be a valuable index for evaluating fetal cardiac function and it has been evaluated as an indicator for predicting pregnancy outcomes in a number of studies. [15][16][17][18][19][20][21][22][23] Evaluation of Mod-MPI depends on comparison to a normal reference ranges, so a large multicentre study using standardised machine settings and techniques with well-defined inclusion and exclusion criteria is still required, which forms the basis of this study. The primary aim of this study was to establish the normal reference ranges of fetal left ventricular (LV) Mod-MPI and time intervals by pulsed…”
Section: Introductionmentioning
confidence: 99%
“…Our results are in accordance with Van Mieghen et al [39] who also reported a higher prevalence of a small LV in fetuses with left CDH but no differences in ventricular function. Other imaging techniques such as tissue Doppler have been also used to evaluate abnormal contractility and myocardial displacement in fetuses with CDH [40,41]. It can be concluded that CDH has an impact on the cardiac chamber shape, size, and function.…”
Section: Our Results In Relation Of What Is Knownmentioning
confidence: 99%
“…Prenatal cohort studies of myocardial function have not to date demonstrated significant fetal cardiac dysfunction (25)(26)(27)(28)(29).…”
Section: Fetal Cardiac Function In Congenital Diaphragmatic Herniamentioning
confidence: 99%